A Megavoltage CT Image Enhancement Method for Image-Guided and Adaptive Helical TomoTherapy - Liu, Yaru; Yue, Chenxi; Zhu, Jian; Yu, Haining; Cheng, Yang; Yin, Yong; Li, Baosheng; Dong, Jiwen (Frontiers in Oncology, 2019)
Purpose: To propose a novel method to improve the mega-voltage CT (MVCT) image quality for helical TomoTherapy while maintaining the stability on dose calculation. Materials and Methods: The Block-Matching 3D-transform (BM3D) and Discriminative Feature Representation (DFR) methods were combined into a novel BM3D+DFR method for their respective advantages. A phantom (Catphan504) and three serials of clinical (head & neck, chest and pelvic) MVCT images from 30 patients were acquired by helical TomoTherapy system. The contrast-to-noise ratio (CNR) and edge detection algorithm (canny) were employed for image quality comparison between the original and BM3D+DFR enhanced MVCT. Simulated rectangular field of 6MV X-ray beams were vertically delivered on original and post-processed MVCT serials of the same CT density phantom, and the dose curves on both serials were compared to test the effects of image enhancement on dose calculation accuracy. Results: Totally 466 transversal MVCT slices were acquired and processed by both BM3D and the proposed BM3D+DFR methods. Compared to the original MVCT image, the BM3D+DFR method presented remarkable improvement in terms of soft tissue contrast and noise reduction. For the phantom image, the CNR of the region of interest (ROI) was improved from 1.70 to 4.03. The average CNR of ROIs for 10 patients from each anatomical group were increased significantly from 1.45±1.51 to 2.09±1.68 for head & neck (p<0.001), from 0.92±0.78 to 1.36±0.85 for chest (p<0.001), and from 1.12±1.22 to 1.76±1.31 for pelvic (p<0.001), respectively. The canny edge detection operator showed that BM3D+DFR provided clearer organ boundaries with less chaos. The root-mean-square of the dosimetry difference on iso-center passed horizontal dose profile curves and vertical percentage depth dose curves were only 0.09% and 0.06%, respectively. Conclusions: The proposed BM3D+DFR method is feasible to improve the soft tissue contrast for the original MVCT images with coincidence in dose calculation and without compromising resolution. After integration in clinical workflow, the post-processed MVCT may be better applied on image-guided and adaptive helical TomoTherapy.